IMPLIKASI KEBIJAKAN BEBAS VISA KUNJUNGAN KE INDONESIA TERHADAP SOSIAL EKONOMI (STUDI KASUS: KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU PADA TAHUN 2016-2019) - Fatima De Castro Rustam; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Tourism is one of the mainstay sub-sectors for national development, especially in Indonesia and can encourage economic growth, through increasing foreign exchange earnings. Bintan Regency is one of the potential areas from its tourism aspect. Therefore, this study will examine how the implementation of the visa-free visit policy on the socio-economic conditions in Bintan Regency in 2016-2019.This research uses descriptive qualitative research methods. Sources come from books, journals, official documents and official websites from the Ministry of Foreign Affairs and the Directorate General of Immigration and interviews with local people. This study describes the implications of the visa-free visit policy to Indonesia on the socio-economic conditions in Bintan Regency in 2016-2019. There are several positive impacts, namely; the desire of the community to learn foreign languages, increase the creativity of the Bintan people, increase the number of tourist visits of foreign tourists, increase the Regional Original Income (PAD) Bintan. Keywords: Visit Visa Free Policy, Foreign Policy, Tourism, Socio-Economy.